Differences Between Effectiveness Of Inmas Acupuncture And Local Points In Back And Shoulder Pain - Purwanto Purwanto; Jatmiko Rinto Wahyu (Jurnal Keterapian Fisik, 2021)
Background: Shoulder pain and low back pain usually arise because of overuse or excessive use. Acupuncture can relax back muscles, waist and shoulders through cutaneosomatic reflex; and increase the release of endorphins so that it can reduce inflammation in back, waist, and shoulders so that it can help relieve pain and restore the function of back, waist, and shoulders. This study aims to determine differences betwen effectiveness of INMAS and local points acupuncture on pain and quality of life in workers with back and shoulder pain. Methods: This study is quantitative quasi experimental design with control group with pre and post test, conducted in July-September 2020 at Verta Medika Acupuncture, Klaten. The population was all patients with shoulder and back pain who underwent acupuncture therapy and the sample was determined by inclusion and exclusion criteria and divided into two groups using simple random sampling. Each group consisted of 15 patients. Data analysis focused on pain scale (NRS) and quality of life (WHO-QoL). Results: INMAS technique was better at reducing pain scale (ρ = 0.001), quality of physical health (ρ = 0.083), quality of psychological health (ρ = 0,000), quality of social (ρ = 0,000), and quality of environmental health (ρ = 0.045). Conclusion: INMAS technique is more effective than local points acupuncture for reducing pain levels and it improves the quality of life. Research using larger population and sample is needed to increase validity and reliability of the study.